Analisis Profesionalisme Guru dalam Mengembangkan Kurikulum Modifikasi Pembelajaran di Madrasah Ibtidaiyah Darul Muttaqin Sadang - Berliane Salsabila Hartono Putri; Pandita Athallah Herdian; Munawwir (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze teachers’ professionalism in developing a modified curriculum at Madrasah Ibtidaiyah Darul Muttaqin Sadang and to identify the supporting and inhibiting factors. This study employs a qualitative approach using a descriptive research design. The research subjects include the school principal and teachers selected through purposive sampling. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis utilized the Miles and Huberman model, which involves data reduction, data presentation, and drawing conclusions. The results indicate that teachers’ professionalism falls into the “good” category, as evidenced by their mastery of pedagogical, professional, social, and personal competencies. Teachers are able to plan, implement, and evaluate learning adaptively. The development of a modified curriculum is carried out through adjustments to learning materials, methods, media, and evaluation. Supporting factors include support from the madrasah principal and teacher motivation, while inhibiting factors include limited training, administrative burdens, and differences in student abilities. The implications of this study indicate that enhancing teacher professionalism through continuous training is essential to support the development of a more effective and inclusive curriculum